2005
DOI: 10.1111/j.1740-0929.2005.00253.x
|View full text |Cite
|
Sign up to set email alerts
|

Selective feeding behavior of calves is affected by basal diet

Abstract: The present study examined the way the selective feeding behavior of calves was affected by basal diet. Three basal diets containing oat hay and concentrate, with the addition of different levels of roughage content (low, medium and high) were prepared by changing their mix ratios. Orchard grass (OG) and Japanese pampas grass leaf (JP) were used as testing foods. In the preliminary phase, all calves were fed each basal diet three times per day and then food selection between JP and OG was examined. Dry matter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 19 publications
0
7
1
Order By: Relevance
“…Consequently, despite different eating behaviour, both genotypes had similar feed intake. Fukasawa et al (2005) reported that genetic differences among breeds may influence intake as well as the eating behaviour of animals. Variations in eating activity observed in goat breeds may result from differences in body size and oral morphology (Provenza et al 2003).…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, despite different eating behaviour, both genotypes had similar feed intake. Fukasawa et al (2005) reported that genetic differences among breeds may influence intake as well as the eating behaviour of animals. Variations in eating activity observed in goat breeds may result from differences in body size and oral morphology (Provenza et al 2003).…”
Section: Resultsmentioning
confidence: 99%
“…They were progeny from the same sire. Two of the three subjects in the present study were the same animals used in a previous study (Fukasawa et al . 2005).…”
Section: Methodsmentioning
confidence: 99%
“…Each diet was formulated to meet the need for total digestive nutritients (TDN) according to the Japanese Feeding Standard for Beef Cattle (Agriculture, Forestry and Fisheries Research Council Secretariat 2000). Details of the diets are described in a previous study (Fukasawa et al . 2005).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, there are reports showing that dairy goats in various genotype may give different response to the feeding systems (Provenza et al 2003;Mellado et al 2004;Fukasawa et al 2005). Therefore, the objective of the current study was to examine the effect of different feeding systems (total mixed ration vs. separate roughage-concentrate) on the milk yield, milk composition, and body weight chance of German Fawn and Saanen does.…”
Section: Introductionmentioning
confidence: 99%